2013
DOI: 10.5539/ies.v6n12p74
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Attitudes toward Students with Disabilities in a Public University in Jordan

Abstract: This study explores the attitudes of higher education (HE) faculty members towards inclusion of students with disabilities at one large public University in Jordan using a survey approach. A total of 170 faculty members completed the survey. The most important findings of this study are: (a) regardless of the academic discipline, the majority of faculty members have positive attitudes toward inclusion of students with disabilities in HE institutions; (b) the majority of the faculty members were not familiar wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
11
0
10
Order By: Relevance
“…É neste sentido que o DC3 refere a carência de "recursos físicos, pedagógicos", e ainda "turmas grandes, pouco tempo para trabalhar com estes estudantes, dificuldades de interação com a turma e docentes". Estes resultados são concordantes com muitos estudos que referem não ser suficiente a boa vontade para que a inclusão dos ENEE seja uma realidade e que é necessário ultrapassar barreiras no que se refere às acessibilidades, mas também as barreiras atitudinais e que têm impacto na inclusão destes estudantes (Abu-Hamour, 2013;Berggren et al, 2016;Cabral et al, 2015;Fossey et al, 2017;Gumbi et al, 2015;Venville et al, 2014). Não obstante o esforço em prol da inclusão, reconhece-se que "para a instituição e às vezes para o próprio aluno acaba por ser muito difícil e é frustrante .…”
Section: Análise E Discussão Dos Resultados Presença E Inclusão Dos Eunclassified
See 2 more Smart Citations
“…É neste sentido que o DC3 refere a carência de "recursos físicos, pedagógicos", e ainda "turmas grandes, pouco tempo para trabalhar com estes estudantes, dificuldades de interação com a turma e docentes". Estes resultados são concordantes com muitos estudos que referem não ser suficiente a boa vontade para que a inclusão dos ENEE seja uma realidade e que é necessário ultrapassar barreiras no que se refere às acessibilidades, mas também as barreiras atitudinais e que têm impacto na inclusão destes estudantes (Abu-Hamour, 2013;Berggren et al, 2016;Cabral et al, 2015;Fossey et al, 2017;Gumbi et al, 2015;Venville et al, 2014). Não obstante o esforço em prol da inclusão, reconhece-se que "para a instituição e às vezes para o próprio aluno acaba por ser muito difícil e é frustrante .…”
Section: Análise E Discussão Dos Resultados Presença E Inclusão Dos Eunclassified
“…Assinale-se que, (Abu-Hamour, 2013;Berggren et al, 2016;Cabral et al, 2015;Couzens et al, 2015;European Commission, 2012;Fossey et al, 2017;Gumbi et al, 2015).…”
Section: Análise E Discussão Dos Resultados Presença E Inclusão Dos Ementioning
confidence: 99%
See 1 more Smart Citation
“…Examining the attitudes of university professors in Jordan on the issue of integration of students with disabilities in higher education, Abu-Hamour (2013) found that most university faculty support the integration of people with disabilities in higher education, despite the fact that no academic regulations on such integration exist. Female professors expressed stronger support toward students with disabilities that did male professors.…”
mentioning
confidence: 99%
“…In Chile and Portugal, as in most Western countries, access to college for people with disabilities is on the rise (Abu-Hamour, 2013;Konur, 2006). However, when we analyse the educational reality it shows that these institutions are the most excluding for them to remain there (Moreno, 2005).…”
Section: Introductionmentioning
confidence: 99%